Safety implementation framework for Pakistani construction industry. (February 2016) - Raheem, Adeeba A.; Issa, Raja R.A.
Highlights: The aim of this study is to improve the existing construction safety situation in Pakistan by developing a framework for better implementation of safety practices and thus bridging the safety related perceptual gaps between the different stakeholders and regulatory authorities. This study provides a clear understanding regarding the current issues that are hindering the proper implementation of safety rules in Pakistan. The proposed safety framework is composed of guidelines for a reciprocal safety implementation system with aspects such as regulatory enhancements and corporate safety culture improvements. Past research studies have presented the analysis of the construction safety situation in Pakistan, but a detailed improvement system has never been proposed. This study can also serve as a model for Pakistan's neighboring countries with similar socioeconomic conditions. Most of Pakistan's neighboring countries have weak/no safety implementation system for their construction industry and these countries have similar resource constraints as Pakistan. Abstract: Despite the Pakistani construction industry's recent rapid growth and development, workers are still working in poor safety conditions. While Pakistan has several occupational safety and health laws, they are too broad to be applied directly to the construction industry. Due to the presence of a weak regulatory system, worker safety is not a principal focus of the construction industry. This paper presents a case study that was conducted to help improve the existing construction safety situation in Pakistan by developing a framework for better implementation of safety practices and thus bridging the safety related perceptual gaps between the different stakeholders and regulatory authorities. The proposed safety framework is composed of guidelines for a reciprocal safety implementation system with aspects such as regulatory enhancements and corporate safety culture improvements. The framework was analyzed using the Delphi method and priorities were defined as rated/ranked by a panel of Pakistani construction safety experts. The emphasis of this framework is to expend all possible efforts to minimize the safety risks for construction workers through stronger regulations and voluntary compliance efforts by all the stakeholders. This case study can serve as a model for other developing countries to further develop and improve their construction safety environment.